Computer vision based fatigue detection using facial parameters. Issue 2 (December 2020) - Balasundaram, A; Ashokkumar, S; Kothandaraman, D; kora, SeenaNaik; Sudarshan, E; Harshaverdhan, A
Abstract: Human face is a clear indicator of the fatigue and tiredness experienced by an individual. There may be many cues that can be derived through the analysis of facial parameters which clearly indicate the tiredness. Most of us feel the fatigue and tiredness but at the same time ignore it due to want of time to complete a task or necessity to complete an important work. However there can be instances when this fatigue may turn fatal. Hence an automated system that can easily predict the fatigue becomes the need of the hour. This work is focussed towards developing an automated application that can detect fatigue by analysing various facial parameters. This work uses Computer Vision and has been implemented using Python programming. The result shows good prediction accuracy when it comes to fatigue prediction using facial parameters.